Evaluation of fisheries management policies in the alien species-rich Eastern Mediterranean under climate change - Ofir, Eyal; Corrales, Xavier; Coll, Marta; Heymans, Johanna Jacomina; Goren, Menachem; Steenbeek, Jeroen; Amitai, Yael; Shachar, Noam; Gal, Gideon (Frontiers in Marine Science, 2023)
Recent decades have witnessed declines in the amount of fishing catch due to changes in the marine ecosystem of the Eastern Mediterranean Sea. These changes are mainly a consequence of direct human activities as well as global warming and the entry of invasive species. Therefore, there is a need to improve fisheries management so that it accounts for the various stressors and uses of the marine environment beyond fishing, while providing sustainable catches and maintaining a healthy ecosystem. The ability to understand, and sustainably manage, the fishing industry relies on models capable of analyzing and predicting the effects of fishing on the entire ecosystem. In this study, we apply Ecospace, the spatial-temporal component of the Ecopath with Ecosim approach, to study the Israeli continental shelf to evaluate the impact of climate change and alternative management options on the ecosystem. We examine several management alternatives under the severe assumption of the RCP8.5 climate change scenario for the region. Results indicate that under business-as-usual conditions, the biomass of the native species will decrease, the biomass of the invasive species will increase, and there will be a decrease in the fishing catch. In addition, of the management alternatives examined, the alternative of prohibition of fishing in the northern region of Israel along with the establishment of a network of marine nature reserves provides the optimal response for the ecosystem and fisheries. The Achziv Nature Reserve is projected to be successful, improving the biomass of local species and reducing, to some extent, the presence of invasive species. These results are consistent with visual surveys conducted inside and outside the reserve by the Israeli Nature and Parks Authority. Furthermore, simulation results indicate spill-over effects in areas close to nature reserves yielding higher catches in those regions.